L2 Teachers’ Pedagogical Thoughts: Variations Across Teachers With Varying Levels of Grit - Shabani, Mohammad Bagher; Ashkani, Parisa; Karimi, Mohammad Nabi (Frontiers in Education, 2022)
Teacher pedagogical knowledge base (PKB) has secured a notable position in research on teacher cognition. One obvious gap in this strand of research concerns variations in teachers’ thought processes in relation to individual difference variables despite indications that PKB is likely to differ across individual differences. To fill part of the void, this study investigated how teachers’ PKB—conceptualized as the frequency and dominance of pedagogical thought units/categories—vary as a function of teachers’ levels of grit. To this end, eight EFL teachers (four High-Grit and four Low-Grit) were chosen to participate in the study. Stimulated recall interviews were used to explore the pedagogical thought units that underlie the teachers’ instruction. The thought units of the two groups were then identified by segmenting, coding and categorizing them. The results showed that there were significant differences between the two groups of teachers in the number and list of dominant pedagogical thought categories. Language Management, Procedure Check, Affective, Self-Reflection, Progress Review, Beliefs, and Problem Check constituted the list of dominant PTCs of High-Grit teachers, whereas Low-Grit teachers’ dominant thought categories included Language Management, Procedure Check, Time Check, Progress Review, and Problem Check. The results advance the scholarship on teachers’ PKB by extending the findings to individual differences.